Permanent neonatal diabetes due to mutations in KCNJ11 encoding Kir6.2: patient characteristics and initial response to sulfonylurea therapy. - Sagen, J; Raeder, H; Hathout, E; Shehadeh, N; Gudmundsson, K; Baevre, H; Abuelo, D; Phornphutkul, C; Molnes, J; Bell, G; Gloyn, A; Hattersley, A; et al. (2004)
Permanent neonatal diabetes (PND) can be caused by mutations in the transcription factors insulin promoter factor (IPF)-1, eukaryotic translation initiation factor-2alpha kinase 3 (EIF2AK3), and forkhead box-P3 and in key components of insulin secretion: glucokinase (GCK) and the ATP-sensitive K(+) channel subunit Kir6.2. We sequenced the gene encoding Kir6.2 (KCNJ11) in 11 probands with GCK-negative PND. Heterozygous mutations were identified in seven probands, causing three novel (F35V, Y330C, and F333I) and two known (V59M and R201H) Kir6.2 amino acid substitutions. Only two probands had a family history of diabetes. Subjects with the V59M mutation had neurological features including motor delay. Three mutation carriers tested had an insulin secretory response to tolbutamide, but not to glucose or glucagon. Glibenclamide was introduced in increasing doses to investigate whether sulfonylurea could replace insulin. At a glibenclamide dose of 0.3-0.4 mg. kg(-1). day(-1), insulin was discontinued. Blood glucose did not deteriorate, and HbA(1c) was stable or fell during 2-6 months of follow-up. An oral glucose tolerance test performed in one subject revealed that glucose-stimulated insulin release was restored. Mutations in Kir6.2 were the most frequent cause of PND in our cohort. Apparently insulin-dependent patients with mutations in Kir6.2 may be managed on an oral sulfonylurea with sustained metabolic control rather than insulin injections, illustrating the principle of pharmacogenetics applied in diabetes treatment.